Optimalisasi Podcast sebagai Media Pembelajaran Inovatif dalam Pendidikan Agama Islam di Era Digital - Abdusshomad, Alwazir (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The advancement of digital technology has brought significant changes to education, including the teaching of Islamic Religious Education (PAI). Conventional methods such as lectures and rote memorization often fail to engage students in the digital era. Therefore, innovation in PAI learning is essential to make it more interactive and relevant, one of which is through podcasts. This study aims to examine the effectiveness of podcasts in enhancing students' understanding, engagement, and interest, as well as their potential as a medium for religious outreach. This research employs a literature review method with a qualitative approach, analyzing recent academic sources. The findings indicate that podcasts facilitate students’ comprehension, increase learning engagement, and serve as an effective medium for religious outreach. However, challenges such as technological access and teachers' digital literacy remain obstacles. Thus, educator training and technological infrastructure improvements are necessary to optimize podcast utilization in PAI learning.